Armenian Traditional Lullaby - Hakobyan, Ani; Hovhannisyan, Karine; Sargsyan, Linda (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Lullabies are a special lyrical genre of folklore and one of the oldest genres in oral folk art. Lullabies were mainly performed by mothers to lull their babies to sleep. Songs of this genre can be considered an essential category in human life regardless of nationality, era, and religious or other affiliation. The necessary “components” of a lullaby are a baby, who needs to be rocked to sleep, a performer (mother, nurse, nanny, etc.), a cradle, and the lullaby proper: spoken words and melody sung under a rocking movement. However, this is only the practical side of the issue, because in many cultures, the creation of a lullaby is more than just a song that accompanies the baby during putting it to sleep. There are examples in Armenian lullabies which at first glance seem unrelated to the function of this genre, i. e. lulling the child to sleep. As a rule, in the refrain of such lullabies, which are thematically far from traditional texts, there is a return to the semantic plot of the song. Some lullabies are closely related to other genres of Armenian folk songwriting, such as “antunis” (exile’s song), lyrical, or historical songs. In Armenian folk lullabies, the minor color of the Aeolian and Phrygian modes predominates. Traditional lullabies can be divided into two types: a) the so- called “established” ones – lullabies with an original and rich melodic image, which passed down from generation to generation, with a large range (quart interval and more), with a complex metro-rhythmic pattern and high artistic value, and b) the so-called “improvisational” lullabies, invented on the spot and performed in improvisational style, with a limited intervallic range (intervals up to quart), with a simple rhythmic pattern and a repeating simple musical motif. Regardless of nationality, lullabies are largely the same in content, theme and character, because their essence is the selfless love for the child. We can state with confidence that the lullaby song, as one of the oldest genres of musical folklore, was formed at the dawn of humanity, incorporating the most expressive and typical features of traditional folk thinking. Օրորը ժողովրդական երաժշտական բանահյուսության հնագույն ժանրերից է։ Այն կարելի է համարել մարդկային կենսագործունեության պարտադիր երեւույթներից մեկը՝ անկախ ազգությունից, դարաշրջանից, կրոնական կամ այլ պատկանելությունից։ Օրորոցային երգերը հիմնականում կատարել են մայրերը՝ երեխաներին քնեցնելու համար։ Երաժշտաբանաստեղծական առումով հայկական օրորները բաժանվում են երկու խմբի. ա/ կայունացած, որոնք փոխանցվել են սերնդեսերունդ. առանձնանում են հարուստ մեղեդիով, կուռ կառուցվածքով, մեծ ձայնածավալով (կվինտա-դուոդեցիմա), ունեն բարդ մետրա-ռիթմական նկարագիր եւ բարձր գեղարվեստական արժեք, եւ բ/ իմպրովիզացիոն, որոնք հորինվում են տեղում՝ հանպատրաստից, ունեն փոքր ձայնածավալ (եռալար, քառալար), ռիթմական պարզունակ պատկեր եւ անպաճույճ անվերջ կրկնվող մեղեդի: Օրորի հիմնական թեման երեխան է, նրա գովքը (բուն օրոր), սակայն հանդիպում են այնպիսի օրինակներ, որոնց բանաստեղծական տեքստը «շեղված է» եւ թվում է, թե երեխային քնեցնելու հետ որեւէ կապ չունի: Նման օրինակներում, որպես կանոն, կրկներգում տեղի է ունենում վերադարձ դեպի օրորի բովանդակությունը։ Որոշ օրորներ սերտորեն կապված են հայ ժողովրդական երգարվեստի այլ ժանրերի հետ, ինչպես օրինակ՝ անտունի (պանդխտության երգեր), քնարական կամ պատմական։ Հոդվածում իբրեւ օրինակ, ներկայացված են պատմական Հայաստանի Արցախ (բուն օրոր) եւ Տարոն նահանգների օրորների մեկական նմուշ, որոնցից երկրորդը Եղեռնի օրերին ծնողներին կորցրած թոռան համար երգված օրորոցային է։ Այն աղերսվում է ողբի ու պատմական ժանրի հետ (երգերի վերծանությունն ու նոտագրումն իրականացրել են հոդվածի հեղինակները): Վստահաբար կարող ենք ասել, որ երեխային քնեցնելու նպատակով օրոր երգել են հազարամյակներ առաջ, երբ չկային ազգ եւ ազգություն հասկացությունները, իսկ այս երեւույթի ձեւավորումից հետո այն դարձել է տեսակի պահպանման երաշխիքներից մեկը, հատկապես փոքր կամ ձուլման վտանգ ունեցող ազգերի պարագայում: Колыбельные – особый лирический жанр устного народного творчества и один из древнейших жанров музыкального фольклора. Колыбельные в основном исполняли матери для убаюкивания своего малыша. Песни этого жанра можно считать одной из обязательных категорий жизни человека, независимо от национальности, эпохи, религиозной и иной принадлежности. Армянские народные колыбельные можно разделить на два вида: а) так называемые устоявшиеся – передаваемые из поколения в поколение, с оригинальной и насыщенной мелодией, с большим диапазоном (квинта-дуодецима), со сложным метро-ритмическим рисунком и обладающие высокой художественной ценностью, и б) так называемые импровизационные – придумываемые на месте и исполняемые в импровизационном стиле, с ограниченным интервальным диапазоном (трихорд, тетрахорд), несложным ритмическим рисунком и незамысловатым повторяющимся музыкальным мотивом. Колыбельные разных народов – независимо от происхождения – по со- держанию, тематике и характеру во многом сходны, т.к. основная их тема – беззаветная любовь к своему малышу. Тем не менее, в армянском народном песенном творчестве немало примеров колыбельных с ярко выраженной исторической, социально-экономической и лирической тематикой. В данной статье, на основе двух песенных примеров, представляющих Арцахский и Таронский регионы исторической Армении (транскрипции и нотации осуществлены авторами статьи), путём сравнительного анализа выявлены типологические особенности вышеуказанных двух видов армянских народных колыбельных. Lullabies are a special lyrical genre of folklore and one of the oldest genres in oral folk art. Lullabies were mainly performed by mothers to lull their babies to sleep. Songs of this genre can be considered an essential category in human life regardless of nationality, era, and religious or other affiliation. The necessary “components” of a lullaby are a baby, who needs to be rocked to sleep, a performer (mother, nurse, nanny, etc.), a cradle, and the lullaby proper: spoken words and melody sung under a rocking movement. However, this is only the practical side of the issue, because in many cultures, the creation of a lullaby is more than just a song that accompanies the baby during putting it to sleep. There are examples in Armenian lullabies which at first glance seem unrelated to the function of this genre, i. e. lulling the child to sleep. As a rule, in the refrain of such lullabies, which are thematically far from traditional texts, there is a return to the semantic plot of the song. Some lullabies are closely related to other genres of Armenian folk songwriting, such as “antunis” (exile’s song), lyrical, or historical songs. In Armenian folk lullabies, the minor color of the Aeolian and Phrygian modes predominates. Traditional lullabies can be divided into two types: a) the so- called “established” ones – lullabies with an original and rich melodic image, which passed down from generation to generation, with a large range (quart interval and more), with a complex metro-rhythmic pattern and high artistic value, and b) the so-called “improvisational” lullabies, invented on the spot and performed in improvisational style, with a limited intervallic range (intervals up to quart), with a simple rhythmic pattern and a repeating simple musical motif. Regardless of nationality, lullabies are largely the same in content, theme and character, because their essence is the selfless love for the child. We can state with confidence that the lullaby song, as one of the oldest genres of musical folklore, was formed at the dawn of humanity, incorporating the most expressive and typical features of traditional folk thinking.
Keywords: Musicology